The Effectiveness of Hypnotherapy on Decreasing Anxiety in Cancer Survivor Undergoing Chemotherapy (Department of Physical Education, Sport, Health and Recreation, 2018)
This research aimed to find out the effectiveness of hypnotherapy on decreasing anxiety in cancer survivor undergoing chemotherapy. This research was conducted on Jerry Lolowang as the main informant using paradigma and qualitative method, to result in a comprehensive understanding on the phenomenon studied. Specifically, this qualitative research employed case study research design – Life History. Four criteria were used: credibility, transferability, dependability, and confirmability. Data validation was carried out using data triangulation on the informant considered as close to Jerry Lolowang. The analysis in this research was conducted in four stages: data collection, data reduction, data display, conclusion verification. The result of interview with Jerry Lolowang as the basketball athlete and had a testicular cancer showed that hypnotherapy is one way of decreasing anxiety during cemotherapy. Cancer is a set of diseases characterized with uncontrolled growth of certain body cell leading to cell damage and other body tissues, and cancer can affect everyone including athletes. Hypnotherapy can help the process of reducing anxiety and curing other medical diseases such as cancer, by improving an individual’s life spirit to always think positively, and not afraid of his injury or illness.